An unusual cause of anemia in cirrhosis: spur cell anemia, a case report with review of literature - Privitera, Graziella (Gastroenterol Hepatol Bed Bench, 2016)
Chronic anemia is common in liver cirrhosis. In this setting, the pathogenesis of anemia is complex and multifactorial. Spur cell anemia is a serious disorder in cirrhotic patients and is associated with poor prognosis. Liver transplantation constitutes the only therapeutic tool. We report a case with severe spur cell anemia in alcoholic liver cirrhosis. In the attempt to investigate the origin of the disorder, we have evaluated the lipoprotein profile and found a significant reduction of apolipoprotein AI and HDL(3 )subclass as a possible cause of the disease.